Pneumomediastinum: a New Look at an Old Problem in a COVID-19 Pandemic - O. Y. Chizhova; I. A. Ruslyakova; I. G. Bakulin; N. A. Prokofieva; A. G. Sushilova; G. M. Glazunova; K. M. Lebedinsky (Общая реаниматология, 2022)
The aim of the study was to identify the risk factors of spontaneous pneumomediastinum and to determine its management strategy in patients with the novel coronavirus infection.Material and methods. Eighteen patients with spontaneous pneumomediastinum (SPM) hospitalized in the Center for Novel Coronavirus Infection of the Mechnikov Northwestern State Medical University from 2020 to 2021 were examined. The control group consisted of 18 persons selected using matched sampling. We analyzed symptoms, medical and life history, comorbidities, physical examination results, laboratory and instrumental data, and disease management of patients in both groupsResults. The groups were comparable by age and sex. Among all patients hospitalized with the novel coronavirus infection, spontaneous pneumomediastinum was registered in 1.3% (n=18). Analysis of symptoms, medical and life history, comorbidities, physical examination results, laboratory and instrumental data and disease management did not reveal significant differences between the groups. At the same time, the proportion of obese patients in the main group was lower than in the control group. Estimation of HR showed that the risk of spontaneous pneumomediastinum development was significantly lower in obesity (HR=0.14; 95% CI: 0.033–0.63, P=0.010).Conclusion. The risk of spontaneous pneumomediastinum is significantly lower in obese patients.